Analysis of Technical Efficiency and Prodction Risk of Oil Palm Farming in Rimbo Ilir District, Tebo Regency - Naura Nabila Ishar -; Saidin Nainggolan; Endy Effran (Politeknik Pertanian Negeri Samarinda, 2025)
This study aims to: describe the implementation of oil palm farming in Rimbo Ilir District, Tebo Regency; analyze the effect of production input use on actual and frontier production of oil palm farming; and analyze the effect of production inputs on production risk in oil palm farming in Rimbo Ilir District, Tebo Regency. The research data were obtained from 80 farmer respondents using the simple random sampling method and supported by secondary data from relevant institutions. Data were analyzed using the Cobb-Douglas production function, Stochastic Frontier Analysis (SFA) with the Maximum Likelihood Estimation (MLE) approach, and the Just and Pope model. The results indicate that production factors consisting of land area, NPK fertilizer, urea fertilizer, and dolomite significantly influence oil palm farm production, while herbicides and labor have no significant effect. The average technical efficiency value shows that farmers have not yet achieved full efficiency in utilizing production inputs, implying that there is still potential to improve productivity. The production risk analysis reveals that certain production inputs increase production risk, while others contribute to its reduction. In conclusion, oil palm farming in Rimbo Ilir District has not yet reached optimal technical efficiency. It is recommended that farmers improve farm management practices, use production inputs appropriately, and receive policy support in the provision of production facilities to enhance productivity and minimize production risks